Bahasa Indonesia dalam Karya Sastra - Siswanto Siswanto (Balai Bahasa Provinsi Papua, 2019)
Literary language is a special language. The specialty of language in literature is shown in processing words and sentences that are all capable of creating a sense of beauty in it. Characteristics of literary language can be seen in the use of language or beautiful aesthetic. No formal grammar that governm the use of language in a literary work. Each author's literary use of language cen be freely according to his own way of conveying thoughts, feelings, ideas.